Research Progress on the Correlation Between Microecological Flora and Endometriosis - LI Maoping; CHANG Heng (Xiehe Yixue Zazhi)
Microecological flora, an important part of the human microenvironment, changes with the changes in the internal and external environments of the human body, and plays an important role in maintaining human body's normal function. Endometriosis (EMs) is a common estrogen-dependent female disease chara-cterized by the growth of endometrial glands and mesenchyme outside the uterine cavity. Existing studies have shown that imbalance of intestinal and reproductive tract flora can trigger local immune-inflammatory responses and cause systemic immune-inflammatory responses through cytokines and metabolic pathways, which in turn participate in the progression of EMs. Thus, the diagnosis and treatment of EMs through microecological flora interventions is one of the hotspots research in this field. This article aims to review the research progress on the correlation between microbial dysbiosis and EMs, with the hope of providing more references for the treatment of EMs.